The effect of responsive web design on the user experience with laptop and smartphone devices - Hussain, Azham; Mkpojiogu, Emmanuel O.C. (Penerbit UTM Press, 2015)
The introduction of smartphones with their accompanying capacity to access the Internet, changed the way the Internet is used.Many people now use mobile devices to browse the Web. However, the varying screen sizes of these devices portend some impact on their users’ experience, as the Web content on the devices vary in size and the navigation of pages are also different in the various devices.The advent of the responsive web design (RWD) philosophy, revolutionized the way Web pages are designed and the way they appear to the users in the various devices.RWD makes Web pages to adjust to the size of any devices’ screen irrespective of the device type.In this study, the effect of responsive web design of the user experience with a laptop and smartphone devices while using the e-Ebola Awareness System, (a Web based health awareness portal for Ebola virus disease), was measured and evaluated. The results revealed that users had a better user experience with Smartphones than with laptops while using the system, however, for most of the metrics collected, users’ experiences with the two device types were not significantly different at 95% level of confidence, implying that for those metrics, the responsive web design had a similar effect on the users’ experiences and attitudes.